Concise Route to Water-Soluble Multi-Walled Carbon Nanotubes - Liu, Peng; Wang, Tingmei (Current Nanoscience, 2010)
An easy strategy was developed for the water-soluble multi-walled carbon nanotubes (MWCNTs) without the length cutting of MWCNTs via the ultrasonic-assisted chemical functionalization with a redox couple ammonium persulfate/diethanolamine at room temperature. The Fourier transform infrared spectroscopy, Raman and X-ray photoelectron spectroscopy analysis of the functionalized MWCNTs conclusively showed that diethanolamino groups were covalently attached onto the sidewalls of the MWCNTs. The thermogravimetric analysis result showed the surface functional group content of the functionalized MWCNTs was 0.66 mmol/g. And the transmission electron microscope analysis showed that the MWCNTs were exfoliated into individual nanotubes. The resultant MWCNTs were dispersed easily in water and the dispersion was stable for more than 4 days.
Keywords: chemical functionalization